Leisure and its impact on youth in the city of Sana’a: Field research - AL- Hasani, Aziz Ahmed Saleh Nasser (Journal of Humanities & Social Sciences, 2021)
This research aims to clarify the importance of time, highlight the reasons that lead to the youth’s leisure, the activities practiced by the youth sample members in their spare time, the negative effects of the leisure on youth, and the solutions or treatments that address the negative effects of the leisure. To achieve the goals, and answer the questions, the descriptive approach was used by interviewing a specific segment of young people residing in the city of Sana’a as a sample for research. The sample size was 168 (researched) young people. Through the results collected from the field research area, their analysis and interpretation, a number of general results were reached, the most important of which are: The leisure hours vary among the sample members from two to five hours per day, and this is confirmed by the data of Table No. (4) and 75% of the respondents A total of 151 individuals from the sample. The results also showed that most of the sample members watch satellite TV channels to occupy their spare time, and this is confirmed by the data of Table No. (9), with 61% of the total research sample. As well as from the results that one of the negative effects of emptiness on young people is an increase in spending on the branches of the chat tree, in order to occupy the free time in eating and chewing the branches of the chat tree in the mouth for several hours, and this is confirmed by the data of Table No. (18), and by 81% of the total members of the research sample.